Genetic support of the causal association between gut microbiome and COVID-19: a bidirectional Mendelian randomization study - Li, Zengbin; Zhu, Guixian; Lei, Xiangye; Tang, Liqiong; Kong, Guangyao; Shen, Mingwang; Zhang, Lei; Song, Lingqin (Frontiers in Immunology, 2023)
The association between gut microbiome and Coronavirus coronavirus disease 2019 (COVID-19) has attracted much attention, but its causality remains unclear and requires more direct evidence.In this study, we conducted the bidirectional Mendelian randomization (MR) analysis to assess the causal association between gut microbiome and COVID-19 based on the summary statistics data of genome-wide association studies (GWASs). Over 1.8 million individuals with three COVID-19 phenotypes (severity, hospitalization, and infection) were included. And 196 bacterial taxa from phylum to genus were analyzed. The inverse-variance weighted (IVW) analysis was chosen as the primary method. Besides, false discovery rate (FDR) correction of p-value was used. To test the robustness of the causal relationships with p-FDR < 0.05, sensitivity analyses including the secondary MR analyses, horizontal pleiotropy test, outliers test, and "leave-one-out" analysis were conducted.In the forward MR, we found that 3, 8, and 10 bacterial taxa had suggestive effects on COVID-19 severity, hospitalization, and infection, respectively. The genus Alloprevotella [odds ratio (OR) = 1.67; 95% confidence interval (95% CI), 1.32-2.11; p = 1.69×10 −5 , p-FDR = 2.01×10 −3 ] was causally associated with a higher COVID-19 severity risk. In the reverse MR, COVID-19 severity, hospitalization, and infection had suggestive effects on the abundance of 4, 8, and 10 bacterial taxa, respectively. COVID-19 hospitalization causally increased the abundance of the phylum Bacteroidetes (OR = 1.13; 95% CI, 1.04-1.22; p = 3.02×10 −3 ; p-FDR = 2.72×10 −2 ). However, secondary MR analyses indicated that the result of COVID-19 hospitalization on the phylum Bacteroidetes required careful consideration.Our study revealed the causal association between gut microbiome and COVID-19 and highlighted the role of "gut-lung axis" in the progression of COVID-19.